In search of molecular approaches to improving cancer therapy efficacy - Cherepenko, E.; Telegeev, G. (Experimental Oncology, 2014)
The study of genome rearrangement sites using full genome sequences is an important approach to revealing the nature of cancer and finding effective ways for cancer treatment. The progress in DNA sequencing could make the procedure of whole genome reading close to routine procedure of lower cost. The personal analysis of rearranged ends (PARE) method used for rearrangement study is reviewed. PARE allows identifying of individual cancer biomarkers making personal medicine possible. Also, the progress in “liquid biopsy” technology based on detection of circulating tumor cells in the patient’s blood is shortly summarized. Another important approach is the discovered phenomenon of synthetic lethality causing cancer cell death due to appropriate combination of mutations in different genes or inhibitors of their protein products. Studies of genome rearrangements and synthetic lethality are considered promising for the development of effective cancer treatment approaches. Key Words: PARE, circulating tumor DNA, circulating tumor cells, liquid biopsy, synthetic lethality, cancer cell.